Correlates and pharmacoeconomic evaluation of treatment delay among new smear-positive pulmonary tuberculosis patients in Caloocan City. - Pena, Imelda G. (2007)
One of the major threats in public health both locally and nationally is tuberculosis. Despite the documented developments in the implementation of the National TB Control Program, the burden of TB remains high in the Philippines and among countries in South-East Asia and in the Western Pacific regions. The third largest city in the country, Caloocan City, reported decreasing trend in the number of registered TB cases from 2002 to 2004. This cohort study explored the factors that were associated with treatment delay, composed of patient delay and health system delay and evaluated the pharmacoeconomic impact of treatment delay through cost-benefit analysis among new smear-positive TB patients who have initiated treatment (at most one moth prior to interview) in 40 Rural Health Units (RHUs) of Caloocan City from June 2006 to January 2007. Patient delay, defined as the duration of time (in days) from 21 days after onset of TB symptoms until first visit to a health facility, had an increase of 75.9% with a median duration of 45 days. Health system delay, defined as the duration of time (in days) from one week after first visit to a health facility until start of TB treatment at the RHU, has an incidence of 75.7% with a median duration of 7 days. Results revealed that patient delay patients with moderate to high fear or stigma were twice more likely to have patient delay than those without fear or stigma (OR = 1.81, 90%Cl: 1.13 ? 2.91, p = 0.038). Further, respondents who had poor level awareness of TB symptoms were 1.5 times more likely to have patient delay than those with good or moderate awareness (OR = 1.45, 90%Cl: 0.999 ? 2.109, p = 0.101). TB patients who belong to the lower ?low? socio-economic status had an OR = 2.45 (90%Cl: 1.02 ? 5.86, p = 0.091) for health system delay than those in the middle SES. Patients who visited first a private health care facility were 36 times (OR = 36.28, 90% Cl: 3.64 ? 361.42, p =0.010) more likely to have health system delay than those who visited first the RHU. The odds of health system delay was 3.4 times (OR = 3.37, 90%Cl: 1.97 ? 5.77, p = 0.000) higher among patients who first visited other government facility than those who first visited the RHU. At the societal perspective, the net societal benefits considered a loss to the society due to initiation of TB treatment with patient delay amounted to Php36,000.00 per patient, meaning the society incurred more costs or losses due to patient delay. However, the society gains as much as Php21,000.00 when a patient started treatment without patient delay. Similarly, when there is health system delay, society suffered total net societal benefits of around Php14,000.00 per patient as loss but gains about Php6,000.00 when a patient started treatment without health system delay. The incremental benefit of TB treatment without patient delay was about Php57,000 while that of TB treatment initiated without health system delay amounted to Php20,000. It is hoped that public health interventions would be aimed at strengthening health education efforts in order to promote public awareness of the utilization of health care services on TB both at the public and private sectors; to increase awareness of TB disease and its symptoms; and to reduce perceived high stigma to TB. Policymakers, NTP supervisors and program managers may utilize the results to serve as guide for assessing the economic impact of NTP with efficient and delayed initiation of TB treatment at the community level. The study may also serve as a guide in making recommendations on program or policy changes that will prioritize efforts of high societal benefits. Recommendations may likewise be made on funding allocation or requests on implementing TB treatment with averted patient and halth system delay at the regional and national level.
Thesis (DrPH Epidemiology)--University of the Philippines, Manila
Keywords: Tuberculosis